2022
DOI: 10.3390/ijms23136985
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Plant Metabolomics and Its Applications in Stress and Single-Cell Biology

Abstract: In the past two decades, the post-genomic era envisaged high-throughput technologies, resulting in more species with available genome sequences. In-depth multi-omics approaches have evolved to integrate cellular processes at various levels into a systems biology knowledge base. Metabolomics plays a crucial role in molecular networking to bridge the gaps between genotypes and phenotypes. However, the greater complexity of metabolites with diverse chemical and physical properties has limited the advances in plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 269 publications
0
26
0
Order By: Relevance
“…An ideal OTCD workflow should have a number of key attributes: (1) it should be performed under mild conditions, (2) provide a high reaction yield on-tissue, (3) prevent the delocalization of analytes, (4) preserve tissue integrity, and (5) provide robust and reproducible results [12] . Through these experiments, we observed that 4-APEBA provided the greatest potential, with a significant sensitivity boost for derivatized abscisic acid, whereas BTA, GT, and DNPH provided enhancement, but were 1.6 to 2.9 log2-fold less responsive (Fig.…”
Section: Potential In Maldi Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…An ideal OTCD workflow should have a number of key attributes: (1) it should be performed under mild conditions, (2) provide a high reaction yield on-tissue, (3) prevent the delocalization of analytes, (4) preserve tissue integrity, and (5) provide robust and reproducible results [12] . Through these experiments, we observed that 4-APEBA provided the greatest potential, with a significant sensitivity boost for derivatized abscisic acid, whereas BTA, GT, and DNPH provided enhancement, but were 1.6 to 2.9 log2-fold less responsive (Fig.…”
Section: Potential In Maldi Analysesmentioning
confidence: 99%
“…[1] However, only about 14,000 metabolites in the plant kingdom have been detected, suggesting that advanced analytical methods are needed to more thoroughly investigate such highly complex metabolomes. [2] This is even more evident at the level of single cells or single cell-types, where volumes and quantities of analytes are low and generally limit detection to only a small set of compounds. [3] Significant advancements in spatially-resolved and cell-specific metabolomics have emerged in the last decade, [3][4] and the use of these technologies have suggested a central role of cellular heterogeneity in biological systems (including plants) under different conditions where bulk measurements would mask relevant mechanistic insights.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, using an untargeted metabolomic approach allows comprehensive assessment of numerous compounds in a single biological sample ( Patel et al., 2021 ). The untargeted approach is especially useful for providing an overview of changes in the plant metabolome under different conditions ( Katam et al., 2022 ). For example, this technique has recently been successfully applied to investigate the metabolic changes induced by seaweed extracts from the kelp, Ecklonia maxima in corn ( Zea mays ) under drought stress ( Tinte et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are an estimated 200 000 to 1 000 000 distinct metabolites in the plant kingdom, where any single plant species can produce tens of thousands of unique metabolites, far more than most other organisms . However, only about 14 000 metabolites in the plant kingdom have been characterized, suggesting that advanced analytical methods are needed to more thoroughly investigate such highly complex metabolomes . This issue is further compounded when considering metabolite levels within single cells, where volumes and quantities of analytes are low and generally detection is limited to only a small set of compounds .…”
mentioning
confidence: 99%